ADAPTIVE CAPABILITY OF PT ASIA TRAN SINERGI FARMA DURING THE COVID-19 CRISIS - Karanina Tarista Audria Jayanti; Marcel Slootweg (Diponegoro Journal of Accounting, 2023)
COVID-19 restriction giving an impact on the business operations and marketing strategies of companies in Indonesia including PT Asia Tran Sinergi Farma, a pharmaceutical company in Indonesia. This study examines how PT Asia Tran Sinergi Farma can adapt to the changing situation. Before the pandemic, the company relied on traditional offline approaches, including frequent visits to healthcare professionals. However, the COVID-19 restrictions limited their ability to engage directly with professionals, prompting the company to digitalize customer interactions and enable remote work. The thesis explores the company's marketing strategies during and after the restrictions, emphasizing adaptability and the use of technology-based approaches to maintain customer engagement. It also compares PT Asia Tran Sinergi Farma with its competitors, highlighting their unique selling points and strategies. The study concludes that the company's ability to adapt and adjust during the crisis, including the adoption of hybrid medico-marketing activities, allowed them to remain competitive and generate profits. The findings underscore the importance of adaptability and resilience in navigating business challenges, as demonstrated by PT Asia Tran Sinergi Farma's successful response to the COVID-19 crisis